2022
DOI: 10.1038/s41598-022-08962-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-Helicobacter pylori Helicobacter (NHPH) positive gastric cancer

Abstract: Genetic analysis and culturing techniques for gastric non-Helicobacter pylori Helicobacter (NHPH) are progressing. NHPH is reported to accompany nodular gastritis, gastric MALT lymphoma, and mild gastritis. However, only a few gastric cancer cases infected by NHPH have been reported. PCR analysis specific for NHPH and H. pylori was performed for DNA from gastric mucosa of 282 Korean gastric cancer patients, who were treated with endoscopic submucosal dissection. For more precise strain detection of NHPH, NHPH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…For example, Helicobacter heilmannii s.s has been found in patients with H. pylori -negative MALT lymphoma, and in animal models, it has also been shown to cause MALT lymphoma [ 23 , 24 ]. Other species with the potential to trigger MALT lymphoma are Helicobacter suis , Helicobacter felis , Helicobacter suis , Helicobacter bizzozeronii and Helicobacter salomnois [ 25 , 26 , 27 , 28 , 29 ]. Interestingly, H. pylori infection has been shown to activate the p38 MAPK pathway, upregulating PD-1 expression by gastric epithelial cells and reducing immune response [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Helicobacter heilmannii s.s has been found in patients with H. pylori -negative MALT lymphoma, and in animal models, it has also been shown to cause MALT lymphoma [ 23 , 24 ]. Other species with the potential to trigger MALT lymphoma are Helicobacter suis , Helicobacter felis , Helicobacter suis , Helicobacter bizzozeronii and Helicobacter salomnois [ 25 , 26 , 27 , 28 , 29 ]. Interestingly, H. pylori infection has been shown to activate the p38 MAPK pathway, upregulating PD-1 expression by gastric epithelial cells and reducing immune response [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study suggesting that Helicobacter infection was a notable occupational hazard among the pig farmers. Researchers (Yasuda et al ., 2022) from Japan reported PCR detection for non- H. pylori Helicobacter (NHPH) in 30 cases, 26 of which were found positive as H. suis and 2 as Helicobacter heilmanii / Helicobacter ailurogastricus . Further study is required to draw a possible association between the zoonotic transmissions of the disease from pig to pig farmers.…”
Section: Discussionmentioning
confidence: 99%
“…37 Yasuda et al recently reported finding H. suis infection even in their patients with gastric cancer. 38 Because there is currently no established method for the clinical diagnosis of H. suis infection, accurate diagnosis of H. suis infection is crucial in order to avoid wasting precious time on the wrong course of treatment.…”
Section: Discussionmentioning
confidence: 99%